miR-30a-3p Regulates Autophagy in the Involution of Mice Mammary Glands - Tian, Lei; Guo, Shancheng; Zhao, Zhiye; Chen, Yuxu; Wang, Chunmei; Li, Qingzhang; Li, Ye (International journal of molecular sciences, 2023)
The mammary gland undergoes intensive remodeling during the lactation cycle, and the involution process of mammary gland contains extensive epithelial cells involved in the process of autophagy. Our studies of mice mammary glands suggest that miR-30a-3p expression was low during involution compared with its high expression in the mammary glands of lactating mice. Then, we revealed that miR-30a-3p negatively regulated autophagy by autophagy related 12 (Atg12) in mouse mammary gland epithelial cells (MMECs). Restoring ATG12, knocking down autophagy related 5 (Atg5), starvation, and Rapamycin were used to further confirm this conclusion. Overexpression of miR-30a-3p inhibited autophagy and altered mammary structure in the involution of the mammary glands of mice, which was indicative of alteration in mammary remodeling. Taken together, these results elucidated the molecular mechanisms of miR-30a-3p as a key induction mediator of autophagy by targeting Atg12 within the transition period between lactation and involution in mammary glands.